Implementation of Electronic Medical Records in Type C Hospitals: Implementasi Rekam Medis Elektronik di Rumah Sakit Tipe C - Rani, Destri Maya; Rizqulloh, Lutfiyah; Widyaningrum, Bajeng Nurul (Procedia of Engineering and Life Science, 2025)
The implementation of Electronic Medical Records (EMR) is a strategic step in supporting the digitization of healthcare services in Indonesia, including in type C hospitals. In line with the National Policy, Ministry of Health Regulation No. 24 of 2022 on Electronic Medical Records, the implementation of EMR is mandatory for healthcare facilities. However, in its implementation, type C hospitals face various challenges that need to be comprehensively examined. This study aims to analyze the implementation of EMR in Type C Hospitals through a literature review. The research method is a literature review of articles published between 2023 and 2025, obtained from the Google Scholar and SINTA databases, with a focus on Type C Hospitals. A total of 10 articles met the criteria and were analyzed further. The results of the study indicate that the implementation of RME in type C hospitals has been underway but is not yet optimal. The most supportive factors include management support, human resource competence, information technology infrastructure, organizational culture, and user training. In addition, several hospitals experienced challenges in terms of data security, system interoperability, and resistance to change. This indicates that the implementation of Minister of Health Regulation No. 24 of 2022 still requires varying degrees of adaptation and readiness at the level of type C hospitals. The conclusion of this study emphasizes that the implementation of RME requires comprehensive readiness, both in terms of technical aspects, resources, and organization. It is recommended that Type C Hospitals enhance user training, strengthen management support, and conduct regular evaluations of the systems used to ensure the sustainability and effectiveness of EMR in accordance with current national policies.